Site-selective conjugation of an anticoagulant aptamer to recombinant albumins and maintenance of neonatal Fc receptor binding. (26th April 2017) - Schmøkel, Julie; Voldum, Anders; Tsakiridou, Georgia; Kuhlmann, Matthias; Cameron, Jason; Sørensen, Esben S; Wengel, Jesper; Howard, Kenneth A
Abstract: Aptamers are an attractive molecular medicine that offers high target specificity. Nucleic acid-based aptamers, however, are prone to nuclease degradation and rapid renal excretion that require blood circulatory half-life extension enabling technologies. The long circulatory half-life, predominately facilitated by engagement with the cellular recycling neonatal Fc receptor (FcRn), and ligand transport properties of albumin promote it as an attractive candidate to improve the pharmacokinetic profile of aptamers. This study investigates the effect of Cys34 site-selective covalent attachment of a factor IXa anticoagulant aptamer on aptamer functionality and human FcRn (hFcRn) engagement using recombinant human albumin (rHA) of either a wild type (WT) or an engineered human FcRn high binding variant (HB). Albumin-aptamer conjugates, connected covalently through a heterobifunctional succinimidyl 4-(N-maleimidomethyl)cyclohexane-1-carboxylate linker, were successfully prepared and purified by high performance liquid chromatography as confirmed by gel electrophoresis band-shift analysis and matrix-assisted laser desorption/ionization time of flight. Minimal reduction (∼25%) in activity of WT-linked aptamer to that of aptamer alone was found using an anticoagulant activity assay measuring temporal levels of activated partial thrombin. Covalent albumin-aptamer conjugation, however, substantially compromized binding to hFcRn, to 10% affinity of that of non-conjugated WT, determined by biolayer interferometry. Binding could be rescued by aptamer conjugation to recombinant albumin engineered for higher FcRn affinity (HB) that exhibited an 8-fold affinity compared to WT alone. This work describes a novel albumin-based aptamer delivery system whose hFcRn binding can be increased using a HB engineered albumin.